Dampak Inovasi Produk dan Reputasi Merek Terhadap Keputusan Menabung: Survei pada Nasabah Bank Muamalat Karawang - Novian Ekawaty; Dhia Husniah Athallah; Fida Nur Auliya Anwar (Jurnal Manajemen Bisnis, 2020)
The purpose of this study was to determine how the relationship between Product Innovation and Brand Reputation of Savings Decisions at Muamalat Bank, Karawang Branch. Data were collected using a questionnaire using a Likert scale. This research was used with descriptive and verification methods with a quantitative approach. The sampling technique used is the nonprobability sampling technique with a sample of 68 respondents. The type of data used in this study is primary data and secondary data. Data analysis using multiple linear regression analysis and hypothesis testing. The results of this study prove that Product Innovation and Brand Reputation have a positive and significant effect on Savings Decisions and influence it together by 77.1%.